A Heuristic Variable Ordering Approach for Fault Tree Conversion to Binary Decision Diagram - Dibaei Asl, Mahdi; Hielscher, Kai-Steffen; German, Reinhard (International Conference on System Reliability and Safety Engineering (SRSE), 2024)
Various methods have been introduced and developed to analyze fault tree diagrams. One of the interesting methods is fault tree conversion to Binary Decision Diagram (BDD). However, the conversion process of fault tree to BDD is challenging, and the variable ordering method plays an important role, as it can reduce the size of the generated BDD. This study proposes a new variable ordering strategy regarding the infix notation of the Boolean function which describes the top event in the fault tree. To evaluate the proposed approach, we have compared it with several similar studies regarding generated BDD size. Moreover, we have conducted comprehensive tests on several fault trees of the FFORT benchmark. Experimental results show that the proposed method is efficient for reducing the complexity of generated BDD
Keywords: reliability analysis; fault tree analysis; binary decision diagram; variable ordering